2004
DOI: 10.1111/j.1365-2621.2004.tb09924.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics for Singlet Oxygen Formation by Riboflavin Photosensitization and the Reaction between Riboflavin and Singlet Oxygen

Abstract: The formation of singlet oxygen by riboflavin and the kinetics and mechanisms of riboflavin degradation in aqueous solution under light were determined. The singlet oxygen formation rate by riboflavin was 2.31 mole oxygen/mL headspace/h of serum bottle. The degradations of riboflavin were 66% in D 2 O and 40% in H 2 O, respectively, under light after 24 h. The results indicate that singlet oxygen is involved in riboflavin destruction under light. The riboflavin destructions were 94.0% and 15.7% with 0 mM or 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 32 publications
6
105
0
3
Order By: Relevance
“…42 These reactions may involve tyrosine residues, 51 advanced glycation end products, 50,52 or changes in secondary or tertiary structure. 53,54 Tyrosine residues in the terminal, telopeptide domains of collagen alpha chains can form pi-pi complexes, 55 leading to dityrosine cross-links. [56][57][58][59] Histidine residues in collagen may produce cross-links in the presence of singlet oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…42 These reactions may involve tyrosine residues, 51 advanced glycation end products, 50,52 or changes in secondary or tertiary structure. 53,54 Tyrosine residues in the terminal, telopeptide domains of collagen alpha chains can form pi-pi complexes, 55 leading to dityrosine cross-links. [56][57][58][59] Histidine residues in collagen may produce cross-links in the presence of singlet oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Both excited singlet and excited triplet states of RF are implicated in the photodegradation reactions by different mechanisms [36,41–42 4647 5057]. …”
Section: Reviewmentioning
confidence: 99%
“…Around 30% of RF is destroyed by sunlight in milk within only 30 minutes of exposure [63]. In the dark, RF is stable and remains unchanged under specified conditions for prolonged periods of time [11,36,64]. In the dry form, RF is not much affected by light while in the solution form it is rapidly degraded to various photoproducts through a variety of reactions under aerobic and anaerobic conditions [11,1415 18,2021 2335 65].…”
Section: Reviewmentioning
confidence: 99%
“…Since chlorophyll increased the oil oxidation of the emulsion under light, DABCO and sodium azide, which are well-known singlet oxygen quenchers (Huang et al, 2004;Lee & Choe, 2008), were added to determine whether singlet oxygen was involved in our reaction system. Changes in hydroperoxide content and headspace oxygen consumption in the emulsion containing chlorophyll after 24 h of oxidation under light were significantly different, depending on the presence of DABCO or sodium azide as shown in Fig.…”
Section: Effects Of Dabco and Sodium Azide On The Photooxidation Of Amentioning
confidence: 99%
“…It has been shown that oil autoxidation in an emulsion system occurs differently from that in a bulk oil system since an interface is present (McClements & Decker, 2000), and thus mass transfer is an important key in the oil oxidation of emulsions (Liu, Fu, Yin, & Liao, 2005;McClements & Decker, 2000). Pigments, such as chlorophyll or riboflavin can cause fast singlet oxygen-related oxidation in emulsions under light (Huang, Choe, & Min, 2004;Lee & Choe, 2008). Depending on the composition of an emulsion, pH varies, which might have different effects on the photooxidation of oil in an emulsion containing sensitisers.…”
Section: Introductionmentioning
confidence: 99%